A cohesive zone model for the elevated temperature interfacial debonding and frictional sliding behavior. (6th April 2015) - Xu, Qiang; Tao, Weiming; Qu, Shaoxing; Yang, Qingda
Abstract: In this study, a cohesive zone model that accounts for the interfacial decohesion and frictional sliding behavior as well as the effect of the residual stress is formulated and implemented for analyzing fiber push-out problems in metal matrix composites at elevated temperature. The proposed model can explore the coupling between the interfacial debonding and frictional sliding behavior within a simple formulation. It has been demonstrated the model, after proper calibration of the interfacial shear strength by available experimental data in the literature, can successfully account for the temperature dependence of the load–displacement curves in the push-out test. A parametric study to investigate other material parameters on the load–displacement response of the fiber push-out test has also been carried out and the results show that the frictional stress has a significant effect on the peak load and the frictional sliding behavior. The matrix yield strength is also important for the interaction between the matrix and the cohesive interface.